Analisis Digital Audit Kualitas Laporan Keuangan Koperasi Simpan Pinjam di Kecamatan Lubuk Pakam - Dwi Saraswati; Nur Aliah (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
The aim of this research is to determine the influence of human resources, internal control systems and information technology on the quality of financial reports in savings and loan cooperatives in Lubuk Pakam sub-district. The type of research carried out is quantitative research. The research was conducted in 6 savings and loan cooperatives in Lubuk Pakam sub-district. The population and sample in this study consisted of 30 respondents. The data source used is primary data obtained using a questionnaire and measured using a Likert scale. Meanwhile, the data analysis method used in this research is the multiple linear regression analysis method with the help of computer software, namely the statistical package for social science (SPSS 25). The results of this research show that: (1) human resources do not partially and significantly influence the quality of financial reports of savings and loan cooperatives. (2) Internal control partially and significantly influences the quality of savings and loan cooperative financial reports. (3) Information technology partially and significantly influences the quality of financial reports of savings and loan cooperatives. (4) Human resources, internal control systems and information technology simultaneously and significantly influence the quality of financial reports of savings and loan cooperatives.